FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERADAAN ZAT PEWARNA DAN PENGAWET TERLARANG PADA MAKANAN JAJANAN DI PASAR-PASAR TRADISIONAL KOTA SEMARANG - Lailya Indha Pramastuti; Mursid Rahardjo; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Foods that contain substances harmful to the body will have a negative impact for people who consume them. Hazardous substances are often found in the banned dyes and preservatives. The National Food and Drug Agency’s investigation in 2015, from 7,806 food samples found 295 samples contained rhodamine B, 216 samples contained formalin, 164 samples contained borax and 5 samples contained methanyl yellow. This study aimed to determine the factors that influence the presence of banned dyes and preservatives in snacks at traditional markets in Semarang. This type of research was explanatory research with cross sectional approach. The study subjects were 49 snack vendors. The results showed the contamination rhodamine B 22.4%, borax 12.2% and formalin 0%. Snack food contaminated is cenil, mutiara, kerupuk gado-gado, and gendar. Snacks that contained banned dyes and preservatives are cenil, mutiara, kerupuk gado-gado, and gendar. Chi-Square test results showed that there was a relation between the level of education (p = 0.005), knowledge (p = 0.001), and attitude (p = 0.001) with the presence of banned dyes and preservatives snacks. The results of descriptive analysis showed that the practice of making snacks is bad. Access of food vendors to get dyes and preservatives fairly easy, dyes and preservatives prices affordable. The government control to the used of banned dyes and preservatives on snacks was still uneven. The conclusion from this study is there is a relationship between the level of education, knowledge, attitudes, and practices with the presence of dyes and preservatives banned on street food. The use of banned dyes and preservatives is carried out by the snack vendors at traditional markets in Semarang. It is necessary to have guidance and control are more evenly to the snack vendors.